2013
DOI: 10.1111/bld.12073
|View full text |Cite
|
Sign up to set email alerts
|

‘My brother likes meeting new people, but don't ask him any direct questions’: involving adults with autism plus learning disability in a qualitative research project

Abstract: Accessible Summary• People who have difficulties in communication and understanding are often excluded from research which is about them • In our research, we wanted to find out how people with autism plus learning disability get on with their brothers and sisters once they are grown up • We met with twelve people with autism along with their brother or sister without disability in a way that we hoped would make them feel relaxed • Meeting the brothers and sisters with autism was important, and it helped us un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
3
13
0
1
Order By: Relevance
“…Often, they consider themselves as a second parent yet they do not obtain any type of compensation for the support they provide. According to Tozer et al (2013), this result is similar to that found among siblings in the general population, yet more particularly, brothers and sisters of children with ASD as feel they have increased long-term commitment and responsibility for their siblings.…”
Section: Advocate the Rights Of Siblings With Asdsupporting
confidence: 75%
See 1 more Smart Citation
“…Often, they consider themselves as a second parent yet they do not obtain any type of compensation for the support they provide. According to Tozer et al (2013), this result is similar to that found among siblings in the general population, yet more particularly, brothers and sisters of children with ASD as feel they have increased long-term commitment and responsibility for their siblings.…”
Section: Advocate the Rights Of Siblings With Asdsupporting
confidence: 75%
“…A sense of uncertainty and tension is evident in some studies with adolescent (Opperman & Alant, 2003;Petalas et al, 2009), and adult siblings (Tozer, Atkin, & Wenham, 2013). Feelings of embarrassment, frustration, and anger occur when siblings of children with ASD feel compelled to deal with the attitudes and reactions of others, and even when they need to explain their sibling's condition to their peers (Petalas et al, 2009).…”
Section: Influence Of the Attitudes Of Others Regarding Asdmentioning
confidence: 99%
“…The purpose of the meeting was to assess the emotional attachment and mutual understanding between siblings and enable the researchers to get a sense of family relationships (see Tozer et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…However, more research is needed on the reluctance of some service users and their families to engage with health services, and more interview studies are needed to identify issues that service users may feel too embarrassed to discuss in public. In addition, interviews using augmented forms of communication are needed for people who find it difficult to engage in verbal conversation (Tozer, Atkin, & Wenham, ). Additionally, there is some evidence that some GPs may perceive health checks as a burden that detracts from care for other patients (Chauhan et al., ), and research into their views and attitudes would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…However, more research is needed on the reluctance of some service users and their families to engage with health services, and more interview studies are needed to identify issues that service users may feel too embarrassed to discuss in public. In addition, interviews using augmented forms of communication are needed for people who find it difficult to engage in verbal conversation (Tozer, Atkin, & Wenham, 2014).…”
Section: Discussionmentioning
confidence: 99%